Marvel-verse. Hawkeye. - Lee, Stan, 1922-2018 (Marvel Worldwide, Inc, 2021)
A collection of Marvel Comics featuring Clint Barton--better known as the Avenger Hawkeye. First, Hawkeye proves his worth when battling the Masters of Evil with the Avengers, then he teams up with Iron Man to take on the Mad Thinker. Later, Barton's past collides with his future when he meets Mockingbird for the first time. Includes stories with Ant-Man, the evil Taskmaster, and his fellow Hawkeye from a younger generation, Kate Bishop.